2004
DOI: 10.1007/s10072-004-0231-6
|View full text |Cite
|
Sign up to set email alerts
|

Public health surveillance and incidence of adulthood Guillain-Barré syndrome in Spain, 1998–1999: the view from a sentinel network of neurologists

Abstract: Temporal variation in Guillain-Barré syndrome (GBS) warrants monitoring in certain situations. This study sought to describe a public-health-based GBS surveillance service in Spain and conduct pilot surveillance in the period 1998-1999. Neurologists from 11 hospitals countrywide, serving a population of 3.9 million, reported all patients, ages 20 years or over, admitted to hospital with suspected GBS. Cases that did not belong to the designated hospital catchment area or failed to fulfill diagnostic criteria a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
22
1
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 0 publications
6
22
1
1
Order By: Relevance
“…The number of age groups for which rates were reported ranged from 3 to 9 (median, 7). Five articles presented both case counts and denominators [17,18,20,22,25] ; 5 articles presented case counts and rates [8,24,27,29,31] ; 1 study provided only rates and we obtained case counts from the authors [21] ; 1 study published only the rates in a line graph and we obtained publicly available census data to generate case counts and denominators [23] , and 1 study published only the rates in a histogram and we obtained case counts and denominators from the authors [26] .…”
Section: Resultsmentioning
confidence: 99%
“…The number of age groups for which rates were reported ranged from 3 to 9 (median, 7). Five articles presented both case counts and denominators [17,18,20,22,25] ; 5 articles presented case counts and rates [8,24,27,29,31] ; 1 study provided only rates and we obtained case counts from the authors [21] ; 1 study published only the rates in a line graph and we obtained publicly available census data to generate case counts and denominators [23] , and 1 study published only the rates in a histogram and we obtained case counts and denominators from the authors [26] .…”
Section: Resultsmentioning
confidence: 99%
“…Most patients diagnosed with GBS will be hospitalised due to the nature of the disease [8,26,32,33,[35][36][37]64] : 3 studies reported small numbers of outpatient or community patients identified in their studies compared with numbers of hospitalised GBS cases [12,32,38] . Ten studies noted the inclusion of mild cases in their studies [16,24,29,33,38,45,46,50,57,59] and the design of other studies implied the inclusion of mild cases: 2 studies using general practitioner records [22,23] , a surveillance study [54] , a door-to-door survey [58] and the record linkage system used by the Mayo Clinic [66] .…”
Section: Study Methodsmentioning
confidence: 99%
“…Of those studies that used mainly hospital records, 2 noted that all patients were given intravenous immunoglobulin or plasma exchange therapy [20,67] , and this implies that only serious cases were included, whereas others reported proportions of patients receiving these therapies of between 24 and 49% for intravenous immunoglobulin and 34-51% receiving plasma exchange [26,27,30,47,61] . Ten studies reported missing mild cases [12,32,36,64,69,70] or reported finding it difficult to detect mild cases if they had not been admitted to hospital [17,25,37,62] .…”
Section: Study Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…U periodu pika bolesti oko polovina pacijenata je vezana za invalidska kolica ili postelju dok se letalni ishod, i pored savremene terapije koja nam stoji na raspolaganju, registruje kod 1-18% pacijenata (8). Smatra se da se težina bolesti razlikuje kod različitih subtipova GBS, ali da zavisi i od podneblja na kom se bolest javlja (9). Akutna motorna aksonalna neuropatija spada u najtežu formu bolesti u Evropi i Sjevernoj Americi, za razliku od Dalekog istoka, gdje bolesnici sa AMAN imaju bolju prognozu (10).…”
Section: Uvodunclassified